PENGGUNAAN METODE SAS DALAM PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN PADA SISWA KELAS I SDN 106162 MEDAN ESTATE - Syarifah Hasibuan (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2019)
This classroom action research aims to determine the application of method learning strategies SAS (Structural Synthetic Analysis) Class I students Even Elementary Semester Neg. 106162 Medan Estate in reading through the application of learning strategies with the SAS method. This study used an interactive qualitative method and a class action research approach conducted in 2 cycles. Each cycle includes planning, implementation, observation and reflection. the subjects of this class action research are even class I students of Neg semester. 106162 Medan Estate. While the object is the SAS Method. From the research conducted by examining the initial condition of students as measured by reading tests and the results of classroom action research with 2 cycles. Based on data analysis, it can be concluded that in cycle 1 student learning completeness in this material the average value is only 66.50 while in cycle 2 by applying learning strategies with SAS methods increasing reaching an average value of 90.00 Student responses also increase, observational data of teacher activity from 59.72% in cycle 1, increasing in cycle 2 to 93.06%. Keywords : Reading Beginning, ability, SA Method